PENGEMBANGAN GAME 3D “EVERPLANE” DENGAN LEAP MOTION - Galang Ihsan Isnanto; Samuel Gandang Gunanto; Agnes Karina Pritha Atmani (Journal of Animation and Games Studies, 2019)
Motion Leap (Hand Motion tracking) is a term for recording hand movements used as digital models and is an additional device that can be connected to a computer and can then be used to replace both mouse and keyboard functions. In the 3D game "Everplane", Leap Motion is used as a game controller and is the main component of the game. The Everplane game is an endless game / endless runner type game. Endless runner is a game where the player's character continues to move forward through the endless world of games. The Everplane game has the concept of exploring space. The process of making 3D games "Everplane" through various data research is needed to meet the needs of game production through three stages, namely Preproduction (Game Design, Character Design and Layout Design), Production (Modeling, Texturing, Design graphic user interface, Music, Leap Setup Motion, Assembly Animating, Programming, and Problem Solfing) and Postproduction (Deploying, Mastering and Merchandise).Keywords: Leap Motion, Everplane game, manufacturing process